Analysis of DCB test of angle-ply laminates including bending-twisting coupling. (15th April 2018) - De Gracia, J.; Boyano, A.; Arrese, A.; Mujika, F.; ,
Abstract: Interlaminar fracture of angle-ply symmetric and anti-symmetric laminates by means of the Double Cantilever Beam test has been analyzed. As the cracked arms are symmetric in both cases, bending-twisting coupling occurs. Nevertheless, the effect of that coupling is different in symmetric and anti-symmetric cases. In symmetric cases, it induces a non-uniform aperture of the arms associated to mode I. In anti-symmetric cases, the effect is a sliding of both arms associated to mode III. The analytic approach of the energy release rate includes those coupling effects. Besides the present approach, experimental results are reduced with a previous approach that does not include coupling effects and with the area method.